Sport and underachievement among protestant youth in Northern Ireland: a boxing club case study. Issue 3 (3rd July 2018) - Ferguson, Kyle; Hassan, David; Kitchin, Paul
ABSTRACT: Published research provides support for the potential of sport to promote social, cultural and personal development. In the UK, a corresponding shift in sports development policy is evident, moving away from achieving sports-related goals towards contributing to the government's social policy priorities. Substantial public-sector investment has been made in 'sport for development' projects as a result. However, other scholars caution against an over reliance on the perceived 'power' of sport to deliver upon sport's often vaunted claims. Strategic priorities determined from the 'top–down' exclude those delivering such projects from involvement in decision-making. This article focuses upon a boxing club situated in one of Northern Ireland's most deprived wards and where the prospects of so called 'hard to reach' young Protestant population remain modest subsequent to the Good Friday Peace Agreement. This article will examine how the club uses sport to improve educational and employability outcomes. Taking into consideration the community context, we conclude that the club offers an example of how sport can be harnessed at an individual (micro) and community (meso) level to contribute towards these priorities. Having identified the key elements of success in practice, the overriding question concerning whether, in a broader sense, the structures exist to permit macro-level impact from a micro- and meso-level project is unpacked and explored.